Fracture Mechanics
DOI: 10.1520/stp34936s
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Ultrasonic and Fracture Toughness Factors in Metallic Materials

Abstract: A heuristic mathematical basis is proposed for the experimental correlations found between ultrasonic propagation factors and fracture toughness factors in metallic materials. A crack extension model is proposed wherein spontaneous stress (elastic) waves produced during mic roc racking are instru-" mental in promoting the onset of unstable crack extension. Material microstructural factors involved in this process are measurable by ultrasonic oo probing. Experimental results indicate that ultrasonic attenuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…The empirical correlations that are exhibited in pigs, 16 through 18 imply that stress wave Interactions are important during rapid (catastropic) crack extension, as under the conditions for determining fracture toughness (Brown and Sraavloy, 1966) , Experimental correlation of ultrasonic attenuation factor and fracture toughness "characteristic length" factor for three motels. The exporimental data agree with theoretical relation given by Equation (9) (Vary, 1979a).…”
Section: Fracture Toughness and Attf Nuattqnsupporting
confidence: 87%
See 3 more Smart Citations
“…The empirical correlations that are exhibited in pigs, 16 through 18 imply that stress wave Interactions are important during rapid (catastropic) crack extension, as under the conditions for determining fracture toughness (Brown and Sraavloy, 1966) , Experimental correlation of ultrasonic attenuation factor and fracture toughness "characteristic length" factor for three motels. The exporimental data agree with theoretical relation given by Equation (9) (Vary, 1979a).…”
Section: Fracture Toughness and Attf Nuattqnsupporting
confidence: 87%
“…There is a well-estab-, listed body of theoretical and experimental knowledge concerning the ultrasonic measurement of olast i c moduli ( Truell et al, 1969;Schroiber et al 1973). Conversely, ultrasonic prediction of tansile and yield strengths, and fract i re toughness are currently ' based on empirical correlations (Vary, 1978b), Proposed models for explaining the above-mentioned empirical correlations invoke the concept of ultrasonic stress wave interactions with material microstructure to the degree where the stress waves actually promote plastic deformation and microcrach extension (van list, 1973;Vary, 1979a), This stress wave interaction concept forms the basis for an ultrasonic approach to defining material--defect interactions as a moans for prodiction of ultimate strengtli and dynamic reaction to applied loads. Illustrative examples of the concept are discussed hereinafter.…”
Section: Preliminary Considimationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that for data in the Rayleigh regime extrapolations based on the empirical constants c and m lead to excellent correlations with mechanical properties (e.g., fracture toughness) 1979;Hull, 1982, 1983).…”
Section: Data Simulation For Curve Fittingmentioning
confidence: 99%